Development Of Al Hadist Learning Media - Anati Rahila (Penerbit Hellow Pustaka, 2025)
As a teacher, it is important to pay attention to the right learning media. Learning media can support the optimization of learning in the classroom. Good learning media will certainly make it easier for students to understand the lesson. Some previous research explains that learning media is very important to be presented in every learning. Based on the point of view of hadith science itself, learning media must be realized actualization in the scope of education. So that educators themselves are not only expected to have intellectual and moral competence but must also have strategic competence in determining learning media. Today some points of view assume that learning media in the scope of Islamic learning, especially al Hadith, is still far behind. This is motivated by several factors. Among them, 1) lack of innovation regarding the development of al Hadith learning media. 2) lack of attention from some parties on the issue. 3) the absence of awareness of some educators regarding the urgency of developing al Hadith learning media. This research uses qualitative research methods with literature study data sources in the form of scientific journals, previous research, documents, magazines, newspapers and books with related problems. This research is aimed at knowing how the development of al Hadith learning media. This study found that the media development of learning media al Hadith is important to improve. The development of learning media can be realized by utilizing several aspects such as through visual learning media that include movement, images or demonstrations.